Issues of child rights and sanctity of life in the abduction of Chibok girls in Nigeria and its effect on family stability (2022)
The havoc various militant groups are wrecking on the sustainability of Nigeria as a nation for some years now calls for a serious attention. This is because, the mass killing and the destruction of properties by these groups have dented the image of the country among the comity of nations. Existing studies on the menace of Ethno-Religious militancy in Nigeria have focused mainly on the political, economic, psychological and social perspectives with little attention paid to how the activities of Boko Haram have impacted negatively on the religious value of sanctity of life. The lacuna in the previous studies on the subject matter necessitated this work. This paper adopted a qualitative approach to first, review the history of Boko Haram, its philosophy, activities, various ways the militant groups have infringed on the rights of the girl child, most especially their rights to life which is considered to be a religious value of sanctity of life. The paper revealed that poverty, unemployment and misconception of religion were the major factors that facilitated the emergence of Boko Haram. It further revealed that their activities have caused psychological trauma and have sent many to their early graves, leaving the affected family members with emotional instability. This paper recommends that Nigerian government should, as a matter of urgency address the root cause(s) of Boko Haram’s agitations by eradicating poverty and generating employment to counter terrorism.